The Representation of Mother’s Role in President Joko Widodo’s Instagram Post: A Multimodal Pragmatic Study - Haryanti, Putri; Saddhono, Kunddharu; Anindyarini, Atikah (Journal of Languages and Language Teaching, 2024)
Communication on social media is not only limited to linguistic elements, but also involves images and visuals. The use of images and visuals on President Joko Widodo's Instagram account raises questions about how effectively these messages are understood and received by various sections of Indonesian society. This research aims to explore the linguistic and multimodal elements of Mother's Day commemorative posts on President Jokowi's Instagram account. This research used a qualitative descriptive method and a multimodal pragmatic approach. The research data is in the form of captions as a linguistic aspect and images as a multimodal aspect in Mother's Day commemorative posts on President Jokowi's Instagram account. The data analysis technique uses a pragmatic approach to examine captions and multimodal analysis to explore uploaded visuals. The research results show (1) pragmatic analysis of captions, there are several forms of illocutionary speech acts, including assertive speech acts (declaring), directive speech acts (giving advice/inviting), expressive speech acts (congratulating), and indirect speech act strategies; (2) multimodal analysis through information value, framing, salience, and sequence represents that mothers have a very important role in contributing to preparing their children for the future, caring for them with love, and participating in roles in public spaces. This post shows that the study of multimodal pragmatics on social media can contribute to conveying complex meanings in representing the mother's role.